Preventive Socialization Against Bullying Behavior In Sendangkulon Sdn Kendal District - A Farisi; Dewi Setyowati; Resha Zulfuaedah; Hilwa Naura Nabila; Risna Milkhatin S (Universitas Palangka Raya, 2024)
The Community of Service Program, is a form of community service from educational institutions to the community as part of the implementation of higher education. One of the work programs of the KKN Posko 128 group is preventive socialization of bullying behavior that often occurs in educational environments. Bullying, whether physical, verbal, relational, or cyber bullying, has a significant negative impact on children's psychological development. Family and social environmental factors play a major role in the formation of children's character, which then has an impact on bullying tendencies. This study aims to analyze the causes and impacts of bullying and offer solutions as preventive measures through family education, social environment, and the active role of schools. By focusing on the role of the family in shaping children's behavior and the importance of the role of schools in preventing and handling bullying cases, it is hoped that it can reduce the incidence of bullying and improve children's psychological well-being.